2021
DOI: 10.3389/fenvs.2021.701610
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soil Microbial Biomass and Enzyme Activities to Natural Restoration of Reclaimed Temperate Marshes After Abandonment

Abstract: Restoration of reclaimed marshes has great effects on soil biological processes. However, the responses of soil microbial properties (microbial biomass and enzyme activities) to natural restoration of reclaimed marshes is poorly studied, especially in a long restoration chronosequence. This study assessed the responses of soil microbial properties to natural restoration and investigated the relationships between soil microbial properties and soil physico-chemical and plant properties. We selected a restoration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…Furthermore, SOC and AN were the main soil environmental factors affecting rice yield (Figure 4), in accordance with previous results [15]. In addition, markedly negative relationships among soil BD, bacterial Shannon diversity index, and rice yield were found in our study; previous studies also had similar reports [44,58].…”
Section: Relationships Among Soil Properties Microbial Community and ...supporting
confidence: 92%
“…Furthermore, SOC and AN were the main soil environmental factors affecting rice yield (Figure 4), in accordance with previous results [15]. In addition, markedly negative relationships among soil BD, bacterial Shannon diversity index, and rice yield were found in our study; previous studies also had similar reports [44,58].…”
Section: Relationships Among Soil Properties Microbial Community and ...supporting
confidence: 92%
“…It was found that SOC, DOC, POC, and MBC were positively correlated with SWC and TN, and negatively correlated with SBD. This is mainly because of the increase of soil moisture for plant litter decomposition and soil microbial activity, which would be helpful to the accumulation of soil organic carbon components together [ 46 ]. The higher the soil moisture content, and soil aeration, the less number of aerobic bacteria, SOC mineralization process is abated, the organic material input is greater than the output, the long-term accumulation of soil organic carbon content increased [ 29 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hydrolysis enzyme activities (βG, NAG, and AP) in degraded peatland were significantly lower than those in natural peatland, this may be due to the sharp decrease in soil organic matter after peat reclamation. Previous studies also reported lower soil enzyme activities in agricultural or farm abandoned peatland than those in natural peatland (Wang et al, 2021). Peat cultivation can lead to rapid organic matter decomposition, and the nutrients released change to mobile forms that can be easily leached (Glina et al, 2016).…”
Section: Responses Of Soil Enzyme Activities To Different Hydrologica...mentioning
confidence: 93%